Verificação da implementação no domicílio das orientações dadas no alojamento conjunto - Yamba-Yamba, Maud Marilyn (1990)
The study deals with the extension of assistance at home in an exploratory type of research. In the first stage, with the base of the referred to authors, were elaborated indicators for orientation/care, lately, validated by 23 nurses who work in the three public Maternity hospitais of Rio de Janeiro. The second stage consisted of vcrification of implemcntation, or not of these indicators at home, the central object of the research. The study was based on a randomly selected sample of 30 mothers and their respective babies up to 28 days of age who were hospitalized in the rooming-in, of one of the public institutions selected for study. The results revealed implemcntation by the mothers with some incorrections, 33 indicators principally connected to Corpal hygiene and Clothing, Breast fceding and Umbilical Cord: 32 indicators were not implemented by all the mothers, dissonance between the answers of the nurses and mothers as to the "orientation given" and "non implementation" at home.